Managing Director's Statement on Strengthening Surveillance : 2011 Triennial Surveillance Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
After inputs from country authorities, outside experts, and staff; after extensive deliberations at the Executive Board; after further guidance from ministers and governors at the IMFC meetings-after all that, we need to move from diagnosis to action. The goal of making surveillance as interconnected as the world economy remains an inherently long-term endeavor. Nevertheless, building on recent progress, we can do better even in the near term. I want to take this opportunity to put forward some specific measures, based on Executive Directors' many thoughtful comments and suggestions (Table 1).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet